2015
DOI: 10.5032/jae.2015.01058
|View full text |Cite
|
Sign up to set email alerts
|

Paxton Revisited: The Essence of the Lived Experiences of Urban Agricultural Education Students

Abstract: The rapidly growing world population and need for more food and agricultural knowledge has inspired city dwellers to explore urban cultivation practices such as vertical farming and community gardening. Ultra-modern approaches to growing crops and livestock in urban highrise buildings has sparked the imagination of scientists, agriculturists, and engineers as well as rural and urban citizens in recent years. With this new piqued interest for urban agriculture, secondary urban Agricultural Education programs ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…As agricultural educators, we recommend the continuance of investigation into community agriculture programs as gateways through which youth are exposed to opportunities to develop prosocial behaviors. Creating agricultural programs that target at-risk youth with the intention of developing both technical agricultural skills, as well as prosocial decision-making skills could both expand the reach of agricultural education to non-traditional audiences and create life-changing educational opportunities for young people (Brown, et al, 2015). One important implication of taking agricultural education to underserved communities may be reconceptualizing the essence of agricultural education -how do we create connections with communities that are bereft of formal agricultural education programs?…”
Section: Implications For Agricultural Educatorsmentioning
confidence: 99%
“…As agricultural educators, we recommend the continuance of investigation into community agriculture programs as gateways through which youth are exposed to opportunities to develop prosocial behaviors. Creating agricultural programs that target at-risk youth with the intention of developing both technical agricultural skills, as well as prosocial decision-making skills could both expand the reach of agricultural education to non-traditional audiences and create life-changing educational opportunities for young people (Brown, et al, 2015). One important implication of taking agricultural education to underserved communities may be reconceptualizing the essence of agricultural education -how do we create connections with communities that are bereft of formal agricultural education programs?…”
Section: Implications For Agricultural Educatorsmentioning
confidence: 99%
“…By showcasing local SBAE SAEs, peer-to-peer interactions were fostered and engaged students in recognizing the relevance between the community and their SAE topic. Brown et al (2015) concluded, a shortcoming of urban programs was the lack of relevance between subject matter and students' daily lives. In this study, the researchers found similar findings for some students; however, the agricultural education teachers in each of the examined cases sought various means to help to reduce this disconnect through various in-class experiences and partnerships with community stakeholders.…”
Section: Conclusion Implications and Recommendationsmentioning
confidence: 99%
“…The previous presented issues of paradoxical SAE philosophy and implementation (Wilson & Moore, 2007), lack of facilities, resources and time (Camp, Clarke, & Fallon, 2000;Retallick, 2010;Wilson & Moore, 2007), and growing concern with meeting the needs of a changing demographic of students (Barrick, et al, 1991;National Research Council, 1988;Retallick, 2010), have caused the relevance of SAE in an urban setting to be questioned. According to Brown, Roberts, Whiddon, Goossen, and Kacal (2015), a lack of student relevance between agriculture subject matter and inner city workings existed. Furthermore, Henry, Talbert, and Morris (2014), suggested that there was a lack of students' perceived connections to practical application of agriculture in urban communities due to unrecognized local agricultural industry.…”
mentioning
confidence: 99%